MODERN APPROACHES TO THE ORGANIZATION OF THE SYSTEM OF CONTINUOUS PROFESSIONAL DEVELOPMENT OF PHYSICAL CULTURE INSTRUCTORS (American Journal of Pedagogical and Educational Research, 2023)
This article reveals the importance of the axiological approach to improving the system of professional development instructors in physical education of Preschool educational organizations.